KEKAYAAN JENIS TUMBUHAN HERBA ANGIOSPERMAE DI TAMAN HUTAN RAYA RADEN SOERJO SUB WILAYAH MOJOKERTO - Nadya Grace Meidy Respitosari; Pujiastuti Pujiastuti; imam Mudakir (FKIP Universitas Jember, 2016)
Raden Soerjo The Indonesian archipelago, The Java Island still has a tropical rain forest area with high diversity of species that located in the Raden Soerjo Grand Forest Park, East Java. The diversity of plant species is an important foundation for forest. One of the species diversity to be maintained is teh herbaceous plant. The herbaceous plant is a plants that have soft and succulent stems, little or no secondary tissue at all. Purpose of the research was to know the type of herbaceous plant in Raden Soerjo Grand Forest Park. This research includes descriptive explorative research. The processes in this study include sampling, identifying, classifying, and calculating spesies richness. The research started from February to March 2018. The research method used cruising method, while the sampling technique is purposive sampling technique. The angiosperm herbaceous that found in Raden Soerjo Grand Forest Park are 1183 plants, consisting of 31 species and divided into 17 families. The families consist of Asteraceae, Araceae, Colchicaceae, zingiberaceae, Commelinaceae, Begoniaceae, Urticaceae, Polygonaceae, Orchidaceae, Amaranthaceae, Acanthaceae, Ranunculaceae, Xanthorrhoeaceae, Pytolaccaceae, Solanaceae, Rubiaceae and Balsaminaceae